A comprehensive survey on enhancement of system performances by using different types of FACTS controllers in power systems with static and realistic load models - Bindeshwar Singh; Rajesh Kumar (Energy Reports, 2020)
In present time the power demand increases more rapidly in the power generation and transmission and distribution system sectors. For maintaining the power system stability and steady state operation of power systems causes from disturbance, faults and suddenly changing of the load, voltage instability, voltage swell, voltage sag, harmonics, and change in frequency, stability is the most important factor for the power systems. Due to instability, different problems occur in power systems such as fluctuation in voltage and frequency, which may cause damage or failure of power systems. This article presents taxonomical survey on optimization techniques for enhancement system performance by FACTS controllers such as Thyristor Controlled Series Capacitor (TCSC), Thyristor Controlled Phase Angle Regulator (TC-PAR), Static VAR Compensator (SVC), Dynamic Voltage Restorer (DVR), Sub-Synchronous Series Compensator (SSSC), Static Synchronous Compensator (STATCOM), distributed-STATCOM, Unified Power Flow Controller (UPFC), Generalized Unified Power Flow Controller (GUPFC), Unified Power Quality Conditioners (UPQC), Unified Dynamic Quality Conditioners (UDQC), Interlink Power Flow Controller (IPFC), GeneralizedInterlink Power Flow Controller (GIPFC) and Hybrid Power Flow Controller (HPFC) etc. in power systems with static and realistic load models. The system performances such as real and reactive power losses, power quality, voltage profile, power system oscillations, loadability of system, reliability and security of system, power system stability, bandwidth of operations, flexible operations, available power transfer capacity, system power factor, environmental etc. are enhanced by optimally placed different types of FACTS controllers in power systems with static and realistic load models. In this survey article will be very much helpful to the researchers and practitioners for finding out the relevant references in the field of enhancement system performances by different types of FACTS controllers in power systems with static and realistic load models.
Keywords: 330; FACTS controllers; Load models; Optimization techniques; System performances; Power systems